Heterogeneity symptoms of urgency in patients with benign prostatic hyperplasia - V. L. Medvedev; M. I. Kogan; T. I. Derevianko; P. V. Shornikov; M. E. Efremov; D. S. Isaeva (Инновационная медицина Кубани)
Background One of the relevant tasks of modern urology is the correct understanding of symptoms of the lower urinary tract (LUTS). The social aspect of overactive bladder syndrome (OAB) and the lack of objective ways for non-invasive diagnostics make it necessary to search for new study methods. There is increasing evidence that urination diary can be a clinically powerful tool for assessing bladder sensation, especially in cases of obtaining information not only about the volume of micturition, but also about the degree of urgency with each individual urination. To date, several tools have been developed to assess the severity of OAB, including the international scale of Overactive Bladder Symptom Score (OABSS), proposed by Y. Homma and J. G. Blaivas in 2006–2007.Objective Тo identify the most significant signs of urgency in men with benign prostatic hyperplasia and overactive bladder with and without detrusor hyperactivity (DH).Material and Methods To assess the OAB, patients completed the OABSS, visual analogue scale (VAS), and also kept urination diaries. After the results were obtained, the severity of symptoms was evaluated, considering the data of the urination diary. All patients underwent a complex urodynamic study (CUDI), the results of which were compared with subjective criteria for the severity of urgency and the most significant clinical signs of detrusor hyperactivity.Results Against the background of the analysis of the data obtained, it was possible to classify nocturia by type in 93 patients. One patient (1.07%) had diurnal polyuria. Nocturnal polyuria was in 39 (41.9%) people. Decreased bladder capacity was found in 43 (46.2%) men. Ten (10.7%) patients had various sleep disorders. The IPSS was 24 ± 0.91, the mean score was 14 ± 0.7 points for irritative symptoms according to IPSS (questions 2, 4 and 7) and 13 ± 0.8 points for obstructive symptoms. From the data reported by CUDI, spontaneous detrusor activity was detected in 49 (43.7%) patients, in 63 (56.2%) it was not registered. When analyzing the VAS, it was found that the urgency in patients with BPH and DH, reflecting the initiation of the urge to urinate, is 31 ± 0.6 mm (p < 0.05). On average the indices of the difficulty of holding the urge are higher by 2.9 ± 0.2 points (p < 0.05) in those patients who have DH. When answering the question "How often cannot you retain urine with a strong sudden urge?", the indicators were recorded higher by 3.1 ± 0.3 points (p < 0.05), in patients with detrusor hyperactivity.Conclusions In patients with BPH and the presence of urgency, the frequency of the urge to urinate is 32% higher, and the difficulty of maintaining the urge is 46% more pronounced, compared with the examined men who do not have detrusive hyperactivity.